Interiors and the legacy of postmodernism - Farrel,Terry (London, United Kingdom : Laurence King, 2011)
Sir Terry Farrell was one of the pioneers of the Postmodern style, as seen in his early TV-am building. This is the first book to focus on his interiors, which helped to develop that style in its heyday and beyond
Keywords: INTERIOR ARCHITECTURE